ANALISIS PENERAPAN E-NOFA (ELEKTRONIK NOMOR FAKTUR) PAJAK SEBAGAI UPAYA UNTUK MENCEGAH TERJADINYA FAKTUR PAJAK FIKTIF DAN FAKTUR PAJAK NOMOR BERGANDA (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO) - Alhabsyi, Muhamad N; Saerang, David P. E.; Budiarso, Novi S. (Universitas Sam Ratulangi, 2018)
The purpose of this study was to find out (e-Nofa) taxes in the tax service office (KPP) in Manado. The type of research conducted is qualitative. Data is obtained by conducting interviews, literature studies, documentation and collecting documents related to research. The data taken are: Sources of information, language, organizational structure, head office and agencies, as well as interviews with the Pratama Manado tax office and taxable entrepreneurs (PKP) who use E-Nofa. The analytical method used is descriptive comparative. The stages carried out in this study are the data needed, after which transcripts of interviews are made. Then an interview is conducted by providing codes to assist in presenting and focusing what data is suitable for analysis. The results showed that the application of e-Nofa at KPP Pratama Manado was good, but it was not yet fully efficient because of some requirements of tax duties that caused an efficient level.Keywords: e-Nofa, Taxable Enterpreneus